Pengaruh model pembelajaran kooperatif tipe inside outside circle terhadap kemampuan komunikasi matematis siswa berbantuan animaker - Anggita, Nabila; Simamora, Minta Ito; Putri, Jihan Hidayah (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
Based on the background of the problem in this research, namely the low mathematical communication skills of class VIII students at the Mawaridussalam Islamic Boarding School due to their lack of mathematical communication skills to learn and participate actively in mathematics lessons, the learning model applied so far seems monotonous which is still centered on teachers and mathematics learning in The Mawaridussalam Islamic Boarding School, especially in terms of building materials, has not implemented the Animaker learning model and media. The aims of this research are: 1) to determine the effect of the Inside Outside Circle type cooperative learning model on the mathematical communication abilities of class VIII students at the Mawaridussalam Islamic Boarding School, 2) to determine the effectiveness of using Animaker media on the mathematical communication abilities of class VIII students at the Mawaridussalam Islamic Boarding School. Based on the results of test calculations at a significance level of a - 5%, it is known that the t count is (19.716 > 2.032), then Ho is rejected and H is accepted, so it can be concluded that there is a significant influence of the Inside Outside Circle type cooperative learning model on students' mathematical communication skills with the help of Animaker. Based on students' mathematical communication skills with the help of Animaker using a student response questionnaire, each student's average score and percentage were obtained in the "Very Good" category. The questionnaire was used to determine student responses to students' mathematical communication skills using the Inside Outside Circle learning model assisted by Animaker